Above-ground biomass and carbon stocks of different land cover types in Mt. Elgon, Eastern Uganda - Buyinza, Joel; Balaba Tumwebaze, Susan; Namaalwa, Justine; Byakagaba, Patrick (International Journal of Research on Land-use Sustainability, 2014)
This research applied selected allometric models to estimate the total above ground biomass (TAGB) and carbon stocks in the different land-use/ land cover (LULC) types in Mt. Elgon National Park, in Eastern Uganda. The LULC types identified for the study were – tropical high forest (THF) - normal, THF- degraded and grasslands. The vegetation in each land cover type was assessed at four levels i.e. the mature trees, poles, saplings and undergrowth. Tree diameter and height of each sampled tree were also measured. In each plot, one sapling was randomly selected, uprooted and sub-samples of the foliage, bole and root components were collected, and their fresh weight was determined in the field. Calculation of the Mean Squared Error (MSE), Prediction Sum of Squares (PRESS) statistic and Predicted R2 values of the selected equations was done to establish the most appropriate equation for biomass and carbon estimation. The TAGB was 652.15t/ha, 55.16t/ha and 41.7t/ha in the THF-Normal, THF-Degraded and Grasslands respectively. The carbon stocks in the THF-normal were 293.65tC ha-1, 25 tC ha-1 in the THF-degraded and 18.76 tC ha-1 in the grasslands. Over 90% of sequestered carbon was lost due to land cover change from THF-Normal to THF-Degraded. This calls for policy makers to urgently come up with interventions to address forest degradation.
Keywords: Biomass; Carbon sink; Land cover change; Mt. Elgon; Uganda